The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/09593985.2018.1424979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mobilization with movement on lateral knee pain due to proximal tibiofibular joint hypomobility

Abstract: This case report describes a 45-year-old female who presented with lateral knee pain over the right proximal tibiofibular joint (PTFJ) managed unsuccessfully with rest, medications, bracing, injection, and physiotherapy. Clinical diagnosis of PTFJ hypomobility was based on concordant symptom reproduction with palpatory tenderness, accessory motion testing, and restricted anterior glide of the fibula. Intervention consisted of Mulligan's mobilization with movement and taping over the right PTFJ with immediate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Also, they reported that the patient was discharged after four treatment sessions of Mulligan's mobilization with movement and taping over the right PTFJ, and nally the patient was pain free and fully functional at the 6th month of her follow-up. However, the case reports of both Kawaguchi et al [30] and Anandkumar et al [21] do not assist us to provide any additional evidences to support the idea of the correlation between lateral knee pain and ACL injury, but a relatively rapid disappearance of lateral knee pain in response to a successful treatment poses the potential use of lateral knee pain in ACLR follow-up.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Also, they reported that the patient was discharged after four treatment sessions of Mulligan's mobilization with movement and taping over the right PTFJ, and nally the patient was pain free and fully functional at the 6th month of her follow-up. However, the case reports of both Kawaguchi et al [30] and Anandkumar et al [21] do not assist us to provide any additional evidences to support the idea of the correlation between lateral knee pain and ACL injury, but a relatively rapid disappearance of lateral knee pain in response to a successful treatment poses the potential use of lateral knee pain in ACLR follow-up.…”
Section: Discussionmentioning
confidence: 81%
“…Also, the case report of Anandkumar et al (2018) described a 45-year-old Canadian female with lateral knee pain over the right proximal tibio bular joint (PTFJ) managed unsuccessfully with rest, medications, bracing, injection, and physiotherapy. Finally, she was clinically diagnosed with PTFJ hypomobility [21]. Also, they reported that the patient was discharged after four treatment sessions of Mulligan's mobilization with movement and taping over the right PTFJ, and nally the patient was pain free and fully functional at the 6th month of her follow-up.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation